ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERINVESTASI DI PASAR MODAL KONVENSIONAL PADA MAHASISWA UNIVERSITAS MERDEKA MADIUN - Evi Dwi Mualifah; Muhammad Imron; novy rachma herawati (JAMER : Jurnal Akuntansi Merdeka, 2022)
The aim of this study is to analyze the factors that influence the interest in investing in the conventional capital market in the students of Universitas Merdeka Madiun. The population in this study were 221 active students who were registered at the Investment Gallery in 2019-2020. The sampling technique used probability sampling with simple random sampling method. Determination of the number of samples using the Slovin formula with a margin of error of 10% obtained as many as 70 respondents. The data analysis technique uses multiple linear regression analysis, coefficient of determination analysis, hypothesis testing using t test and F test, and classical assumption test with the help of the IBM SPSS Statistics 25 program. The results show that: 1) Investment understanding partially has a significant effect on interest student investment. 2) Risk partially has no effect on student investment interest. 3) Return partially has a significant effect on student investment interest. 4) Simultaneously shows that understanding of investment, risk, and return has a significant effect on student investment interest. Based on the results of the Adjusted R Square of 51.3%, it means that there are still 48.7% of other variables that affect the interest in investing in the conventional capital market for the students of Universitas Merdeka Madiun.